Clinical Profile of Hypertensives at The Cardiology Consultation - ABDELBAKI, M.; KHELAFI, N.; EL HACHEMI, A.; BEN MESSAOUD, H. (Clinical Medicine And Health Research Journal, 2023)
Systemic hypertension is a global public health problem. It affects all parts of the population. In Algeria, according to the TAHINA 1 study, high blood pressure is the most common chronic pathology (24.8%). Despite numerous recommendations from learned societies 2.3.4.5 and the existence of effective therapies, a high percentage of patients remains uncontrolled 6.7.8. Our work aimed to study the clinical profile of hypertensives who presented to our cardiology consultation at the EPH in Laghouat. This is a longitudinal observational study running from October 2022 to June 2023. We collected 560 patients during daily consultations, lasting 10 months. The results made it possible to describe the present risk factors, dietary habits and socioeconomic conditions.